Normatization of the Symbol Digit Modalities Test-Oral Version in a Latin American Country - Vanotti, Sandra (2014)
The aim of this study was to standardize the Symbol Digit Modalities Test (SDMT)-Oral version in a healthy population living in Argentina and to analyze the influence that age, gender, and education have on the SDMT. Secondarily, it is intended to analyze the performance of patients with multiple sclerosis (MS) on this test. Two hundred ninety-seven healthy participants were evaluated; they had an average age of 39.28 years and 13.87 years of schooling; 77.8% were women. The sample was segmented according to age in three groups: younger than 35 years old, 36 to 50 years old, and 51 to 70 years old. The sample was also segmented according to years of schooling in three groups: 11 years or less, 12 to 16 years, and more than 16 years. All participants were evaluated with the oral version of the SDMT. A clinical sample of 111 patients with MS was also assessed. The mean on the SDMT for the total sample was 51.34 (SD¼12.76). The differences were significant between all groups, p<.05, according to age. The participants with a higher level of education performed better than did those with moderate education and those with less schooling, p<.05. There was a significant difference between patients with MS and healthy controls, p<.01.The SDMT is influenced by age as well as by schooling, although not by gender. The norms displayed here will be useful to accurately evaluate the yield of the patients in the neuropsychological clinic when comparing them with their group of reference. It was also demonstrated that the SDMT can discriminate between patients with MS and healthy people.